The transformation of work and employment relations: Labour and Industry three decades on. (2nd January 2018) - Arrowsmith, Jim
ABSTRACT: This article introduces a Special Issue to mark thirty years of Labour and Industry: a Journal of the Social and Economic Relations of Work . It briefly contextualises and summarises the invited articles that comprise the Special Issue, four of which are reflections by the author(s) on developments since the publication of their earlier landmark paper by the Journal.